O ensino de Sociologia no contexto de ascensão da extrema direita no Brasil - Bodart, Cristiano das Neves; Pires, Welkson (Latitude, 2023)
This article presents the place and role of school Sociology in the current Brazilian context, marked by the rise of far-right ideologies and practices, specifically its ultra-liberal economic bias and moral conservatism. Organized into three parts, it outlines the macro-political, curricular scenario, and some of its implications in school practices, respectively. The primary effort is to reflect on how school Sociology has been - ambiguously - understood and utilized in the Brazilian context. The reflections are supported, in addition to the literature review, by the analysis of the current situation, political-institutional developments, curricular documents, and teacher experience reports collected in the year 2022. Keywords: Brazilian context. Far-right. Curriculum. School practices. School Sociology